Монетарната политика и макроекономската стабилност: теорија и искуства од развиените земји - Силјаноски, Игор (Економски факултет, УКИМ, Скопје, 2014)
Over the time period between 1973 and 2008 the science and practice of monetary policy has evolved. The result is a more efficient mechanism of achieving price stability that has greatly contributed to the achievement of overall macroeconomic stability. In terms of monetary policy, the near collapse of the financial system in the United States and the key industrial countries on the European continent in 2008 highlights some essential questions about the role of monetary policy in preventing the recession: has monetary policy failed to act to prevent the economic crisis and a prolonged recession? Can monetary policy control the factors that led to the financial crisis in 2008? What is the role of monetary policy in achieving macroeconomic stability? Can monetary policy prevent significant financial crisis? In search for answers to these questions the dissertation examines monetary policy theory and conduct some 35 years prior to the financial crisis of 2008. The conclusions of the study illustrate the complexity of the role of monetary policy as well as its acute institutional and theoretical limitations. The dissertation finds that monetary policy achieved the goal of price stability but failed to achieve or preserve other important macroeconomic goals. There are institutional and theoretical reasons for its failures. Central banks have also been very successful at placing the value of money as a focus for monetary policy. Their pronounced focus on price stability under the inflation targeting, however effective in achieving price stability, may have missed the mark on preventing a serious financial and economic crisis in the making. The consensus that monetary policy is better in dealing with the consequences of the crisis than preventing a crisis caused by other non-monetary factors is yet to be tested regarding the latest crisis. Finally, the dissertation provides an overview of monetary policy theory and conduct that provides ideas and solutions that can be reapplied to current and future monetary policy challenges.
Monetary policy and macroeconomic stability: theory and experience of the industrialized countries
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Горан Петревски.
Keywords: monetary policy, central banking, monetary targeting, inflation targeting, monetary theory, monetary policy regimes, monetary policy in industrialized countries.